Formalizing the Shadow Economy in Serbia: Policy Measures and Growth Effects - Krstić, Gorana; Schneider, Friedrich (Contributions to Economics, 2015)
Economic Policy; Public Economics; Economic Growth; Econometrics; Development Economics; Macroeconomics/Monetary Economics//Financial Economics